A NIR light-activated PLGA microsphere for controlled release of mono- or dual-drug. (December 2022) - Wang, Yiyu; Yu, Wenlong; Niu, Chunqing; Yu, Guiting; Huang, Xin; Shi, Jian; Ma, Da; Lin, Xuezheng; Zhao, Kai
Abstract: Microspheres produced from biodegradable poly (D, L-lactic-co-glycolic acid) (PLGA) have been studied widely as drug delivery carriers for therapeutics. This study aimed to develop a near-infrared (NIR) light-activated PLGA microsphere loaded with two kinds of drugs with different molecular weights respectively or simultaneously by the double emulsion method (bovine serum albumin (BSA) and tetracycline hydrochloride (TH) as the drug model agents, indocyanine green (ICG) as the NIR responsive component). To optimize the incorporation of drugs and particle size for PLGA microspheres loaded single drug, the effect of three processing parameters, including the amount of polymer, initial ICG content, and initial BSA or TH content on the drug entrapment efficiency (EE), drug loading and the particle size were investigated. The PLGA microspheres were spherical and ranged from 5 to 10 μm in diameter. The EE of ICG and BSA in PLGA@ICG-BSA was 78.41 ± 0.71% and 69.88 ± 5.14%, respectively. The EE of ICG and TH in PLGA@ICG-TH was 71.52 ± 5.07% and 28.39 ± 3.39%. The PLGA microspheres exhibited desirable biodegradability and low cytotoxicity. Based on the optimized processing of single drug-loaded microspheres, dual-drug-loaded microspheres containing both large and small molecule drugs were further prepared. The EE of ICG, BSA, and TH was 83.37 ± 0.59%, 52.65 ± 3.48%, and 12.88 ± 2.53%; the particle size was ∼7.21 μm. All the NIR-responsive PLGA microspheres exhibited an efficient photothermal property and enhanced photothermal stability under multiple NIR irradiation cycles. The drugs from the different PLGA microspheres were released continuously over 18 days, mainly determined by Fick's diffusion. Furthermore, the drugs can be controlled released through a NIR light trigger, resulting in a dosage increase at a specific time point. Graphical abstract: Image 1 Highlights: A NIR light-activated PLGA microspheres were prepared successfully by the double emulsion method. More than 70% of ICG can be encapsulated by each kind of PLGA microsphere. These NIR responsive microspheres showed efficient photothermal conversion and great photothermal stability. The model drugs can be released from the PLGA microspheres quickly and controllably under NIR irradiation.